Evaluating LLM-driven User-Intent Formalization for Verification-Aware Languages - Lahiri, Shuvendu (Formal Methods in Computer-Aided Design (FMCAD'24), 2024)
Verification-aware programming languages such as Dafny and F* provide means to formally specify and prove properties of programs. Although the problem of checking an implementation against a specification can be defined mechanically, there is no algorithmic way of ensuring the correctness of the user-intent formalization for programs – that a specification adheres to the user's intent behind the program. The intent or requirement is expressed informally in natural language and the specification is a formal artefact. The advent of large language models (LLMs) has made strides bridging the gap between informal intent and formal program implementations recently, driven in large parts due to benchmarks and automated metrics for evaluation. Recent work has proposed evaluating [user-intent formalization] problem for mainstream programming languages [endres-fse24]. However, such an approach does not readily extend to verification-aware languages that support rich specifications (containing quantifiers and ghost variables) that cannot be evaluated through dynamic execution. Previous work also required generating program mutants using LLMs to create the benchmark. We advocate an alternate approach of [symbolically testing specifications] to provide an intuitive metric for evaluating the quality of specifications for verification-aware languages. We demonstrate that our automated metric agrees closely with mostly GPT-4 generated and human-labeled dataset of roughly 150 Dafny specifications for the popular MBPP code-generation benchmark, yet demonstrates cases where the human labeling is not perfect. We believe our work provides a stepping stone to enable the establishment of a benchmark and research agenda for the problem of user-intent formalization for programs.